DISCURSIVE CONVERGENCE AND THE LEGITIMATION OF EDUCATIONAL CRITICISM IN INDONESIA'S DIGITAL PUBLIC SPHERE - Kiki Saepul Anam; Dadang Rahmat Hidayat; Gema Nusantara Bakry (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Despite the growing body of research on digital public discourse, limited studies have examined how educational criticism gains social legitimacy through discourse interactions using a Discourse Network Analysis (DNA) approach. The growing use of digital media has transformed the ways public opinion is formed and negotiated around social issues, including education. In Indonesia, alternative media platforms increasingly function as spaces where citizens discuss and evaluate educational policies and practices. This study examines how educational criticism gains legitimacy within Indonesia’s digital public sphere through public discourse on YouTube. Employing a critical paradigm, the research uses Discourse Network Analysis (DNA) to analyze public responses to the video Fondasi Keropos Pendidikan Indonesia published on the Malaka Project YouTube channel. A total of 1,706 comments were collected, of which 1,025 valid comments generated 2,376 statements involving 886 actors and 15 concepts. The coding process achieved a satisfactory intercoder reliability score (Krippendorff’s Alpha = 0.854). The findings reveal that educational criticism emerged as the most dominant concept within the discourse network and occupied a central position in connecting various educational issues. The distribution of discursive positions shows that 68.5% of actors expressed agreement with the criticism, while 31.5% expressed disagreement, indicating a pattern of discursive convergence rather than polarization. The actor–concept affiliation network further demonstrates that Malaka Project functions as an alternative media platform that facilitates public discussion, discursive convergence, and the social legitimization of educational criticism. This study contributes to the literature by demonstrating how discourse network structures can reveal the processes through which educational criticism becomes collectively validated within digital public spheres. These findings suggest that YouTube operates as a digital public sphere where alternative media can shape collective understanding and strengthen the legitimacy of educational criticism in contemporary Indonesia.